PENGGUNAAN ALGORITMA CLUSTERING K-MEANS UNTUK MENGELOMPOKKAN POLA CUACA - Rinaldi, Ilham; Harmayani, Harmayani (Smart Education, 2025)
Abstract: Weather pattern analysis is crucial for enhancing disaster preparedness and mitigation in Indonesia, particularly in the face of climate change and extreme weather conditions. This study applies the K-Means algorithm to cluster daily weather data obtained from the Meteorology, Climatology, and Geophysical Agency (BMKG). Using average temperature (Tavg) and average humidity (RH_avg) as variables, the data were analyzed to identify two primary weather patterns: